Formula Penyederhanaan Jumlah Partai Politik Di Parlemen Pada Pemilihan Umum Indonesia - NICO HANDANI SIAHAAN (Program Magister Ilmu Politik, Universitas Diponegoro, 2016)
AbstractFormula of maximum threshold figures are naturally able to suppress or reduce the amount of political party. The effectiveness of parliamentary threshold index number is relevantly proven to simplify the number of political parties as well. If the maximum threshold figure formula is applied in conjunction with downsizing allocation of seats in the constituency, it will have an impact on the growth of ENPP Index. This formula will be able to form simple multiparty system in the Indonesian parliament.Keywords: Parliamentary threshold, Political Party, Elections